b+(-7b)+b+b+b+b=

Simple and best practice solution for b+(-7b)+b+b+b+b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b+(-7b)+b+b+b+b= equation:


Simplifying
b + (-7b) + b + b + b + b = 0

Combine like terms: b + (-7b) = -6b
-6b + b + b + b + b = 0

Combine like terms: -6b + b = -5b
-5b + b + b + b = 0

Combine like terms: -5b + b = -4b
-4b + b + b = 0

Combine like terms: -4b + b = -3b
-3b + b = 0

Combine like terms: -3b + b = -2b
-2b = 0

Solving
-2b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Divide each side by '-2'.
b = 0

Simplifying
b = 0

See similar equations:

| 8=k-11 | | (x+1)(x-4)+3x=0 | | y/4=-5.4 | | 12v=5 | | 5(x^2+2)=30 | | 32/4^2 | | 4/32= | | z+11=12 | | 35+10x+3=175 | | 22x-20=-9 | | 20-2=6n-2n | | 27+p=43 | | 12=y-11 | | 50+(x+25)+(2x)=180 | | 1/4*-32 | | 12x+4-16x=22 | | -6x+5(-2x-6)=-40-6x | | x-y=.2 | | x-y=.19 | | 3xy+4x+y=15 | | 3(3x-2)+21=7x+3 | | 9x+2-10x= | | 39=w | | 3(3x-2)+21=7x | | -3k=7(k-20) | | -39=w | | 11=4(x-1) | | x^2-100x+3025=0 | | r/(-51)=-156 | | -w=39 | | 5x+27=4x+28 | | -22p-6(6-5p)=4(p-3)-36 |

Equations solver categories